High CTI flame retardant and high temperature resistant nylon composite material and preparation method and application thereof

By preparing high CTI flame-retardant and high temperature-resistant nylon composite materials, the problem of difficult to develop high CTI, flame-retardant, corrosion-resistant and high-strength functional materials in the existing technology has been solved, and multiple performance improvements of composite materials have been achieved, suitable for new energy vehicles. Components such as electrode sheets and damping sheets.

CN117659691BActive Publication Date: 2025-02-07NINGBO HEYU NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311687447.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-02-07
Estimated Expiration
2043-12-11

AI Technical Summary

Technical Problem

It is difficult to develop a high-performance functional material with high CTI, flame retardant, corrosion-resistant and high strength, especially suitable for components such as new energy vehicle electrode sheets and damping sheets.

Method used

High CTI flame retardant and high temperature resistant nylon composite materials, including high temperature resistant nylon, fiber, flame retardant, synergistic agent, toughener and thermal stabilizer, are prepared through high-speed mixing and twin-screw extruder processing to prepare excellent performance composite material.

Benefits of technology

实现了复合材料的高CTI值、阻燃性能、耐腐蚀性和力学性能的显著提升,满足新能源汽车电极片和阻尼片等构件的高性能需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004598047550000151
    Figure BDA0004598047550000151
  • Figure BDA0004598047550000161
    Figure BDA0004598047550000161
Patent Text Reader

Abstract

The present invention discloses a high CTI flame-retardant and high temperature resistant nylon composite material and its preparation method and application. The material comprises the following raw material components in parts by weight: 50-80 parts of high temperature resistant nylon, 5-30 parts of fiber, 5-15 parts of flame retardant, 1-5 parts of synergist, 3-5 parts of toughening agent, and 0.1-2 parts of thermal stabilizer; the fiber is one or more of carbon fiber and glass fiber; the flame retardant is one or more of aluminum hypophosphite and silsesquioxane; the synergist is nano-silica or nano-silica masterbatch. The material has excellent CTI resistance, corrosion resistance, flame retardancy and mechanical properties, and can be used to manufacture components such as electrode sheets and damping sheets for new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin polymer materials, and in particular to a high CTI flame-retardant and high-temperature resistant nylon composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles and electronic information industries, people have put forward more and higher requirements on the performance of polymer materials. Electrode sheets, damping sheets, etc. are key components of new energy vehicle electronics, batteries, sensors, etc., which need to meet the characteristics of CTI (leakage tracking), flame retardancy, high temperature resistance, high strength, corrosion resistance, electromagnetic interference resistance, as well as good stability, reliability and long life cycle. PA10T is a kind of bio-based semi-aromatic high-temperature resistant nylon material obtained by melt polycondensation of terephthalic acid and decanediamine. It has excellent mechanical properties, heat resistance, dimensional stability, chemical corrosion resistance, hydrolysis resistance and good processing performance, and low water absorption. Therefore, Switzerland EMS, France Arkema, Germany Evonik, Japan Unitika, Shanghai Jieshijie, Kingfa Technology, Wison, Guangdong Longjie, GCL New Materials, etc. have launched their own PA10T products, which play an important supporting role in the development of industries such as automobiles, electronic appliances, etc.

[0003] There have been many reports on the flame retardancy and CTI resistance of aliphatic nylons, but there are fewer reports on aromatic nylons including PA10T. For example, Chinese patent ZL202011598410.2 discloses a synthesis method of a semi-aromatic nylon resin with a high CTI value and a composition preparation technology thereof. Chinese patent ZL202210263595.4 discloses a CTI-resistant red phosphorus flame-retardant semi-aromatic nylon composition, and the red phosphorus flame retardant used is a microcapsule-coated red phosphorus masterbatch. However, the development of a high-performance functional material with high CTI, flame retardancy, corrosion resistance, and high strength for automotive and electronic applications is an urgent problem to be solved in the industry. Summary of the invention

[0004] In view of the shortcomings of the existing technology, the technical problem to be solved by the present invention is to provide a high CTI flame-retardant and high-temperature resistant nylon composite material and its preparation method and application. The material has excellent CTI resistance, corrosion resistance, flame retardancy and mechanical properties, and can be used to manufacture new energy vehicle electrode sheets, damping sheets and other components.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention discloses a high CTI flame-retardant and high-temperature resistant nylon composite material, comprising the following raw material components in parts by weight: 50 to 80 parts of high-temperature resistant nylon, 5 to 30 parts of fiber, 5 to 15 parts of flame retardant, 1 to 5 parts of synergist, 3 to 5 parts of toughening agent, and 0.1 to 2 parts of thermal stabilizer; the fiber is one or more of carbon fiber and glass fiber; the flame retardant is one or more of aluminum hypophosphite and silsesquioxane; the synergist is nano-silica or nano-silica masterbatch.

[0006] Preferably, the silsesquioxane is octamethyloctasilsesquioxane.

[0007] Preferably, the high temperature resistant nylon is PA10T.

[0008] Preferably, the toughening agent is one or more of olefin-acrylate-maleic anhydride copolymers and derivatives thereof.

[0009] Preferably, the heat stabilizer is bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, or a combination of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl tin mercaptan.

[0010] Preferably, the toughening agent is ethylene-acrylate-maleic anhydride copolymer.

[0011] Preferably, the composite material comprises the following raw material components in parts by weight: 73-74.5 parts of high temperature resistant nylon, 30 parts of fiber, 8 parts of flame retardant, 1.5 parts of synergist, 5 parts of toughening agent, and 1.2 parts of heat stabilizer.

[0012] Preferably, the composite material comprises the following raw material components in parts by weight: 73 parts of PA10T, 30 parts of carbon fiber, 6 parts of aluminum hypophosphite, 2 parts of octamethyl octasilsesquioxane, 1.5 parts of nano-silica, 5 parts of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan.

[0013] The second aspect of the present invention discloses a method for preparing the above-mentioned high CTI flame retardant and high temperature resistant nylon composite material, comprising the following steps:

[0014] S1: weighing the raw materials of each component according to weight, and uniformly mixing the high temperature resistant nylon, the flame retardant, the synergist, the toughening agent, and the heat stabilizer in a high-speed mixer to obtain a stirred mixture;

[0015] S2: the stirred mixture obtained in step S1 is fed into the main feeding hopper of a twin-screw extruder, the fiber is fed into the fiber inlet of the twin-screw extruder, and the material is mixed and extruded through the twin-screw extruder;

[0016] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain the high CTI flame-retardant and high-temperature resistant nylon composite material.

[0017] Preferably, in step S2, the temperature of each zone of the twin-screw extruder is set at 290-350° C., and the main engine speed is 300-1000 rpm.

[0018] Preferably, in step S2, the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is 325°C, the main engine speed is 750rpm, the main feed speed is adjusted to control the amount of mixture added, and the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added.

[0019] The third aspect of the present invention discloses the application of the above-mentioned high CTI flame retardant and high temperature resistant nylon composite material in new energy vehicles.

[0020] Compared with the prior art, the advantages and positive effects of the present invention are: providing a high CTI flame-retardant and high-temperature resistant nylon composite material and its preparation method and application, the material has excellent CTI resistance, corrosion resistance, flame retardancy and mechanical properties, and can be used to manufacture new energy vehicle electrode sheets, damping sheets and other components. Specifically:

[0021] (1) The composite material of the present invention adds carbon fiber and alkali-free glass fiber in a specific proportion, which not only plays an excellent reinforcing and modifying role, but also improves the mechanical properties, chemical corrosion resistance and good thermal conductivity of the composite material.

[0022] (2) The composite material of the present invention can not only significantly improve the flame retardant properties of the composite material, but also improve the CTI value of the material through the optimized combination of the flame retardant and the synergist.

[0023] (3) In the preferred embodiment, the composite material of the present invention uses a multi-polymer toughening agent, which can significantly improve the high and low temperature impact resistance of the composite material and further improve the bonding performance between the glass fiber and the high temperature resistant nylon.

[0024] (4) In a preferred embodiment, the heat stabilizer of the present invention is a combination of a piperidinyl diacid ester and methyl tin mercaptan, which further improves the thermal stability of the composite material under high temperature environment or wet heat aging. DETAILED DESCRIPTION

[0025] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the specific structures, process conditions and results described in the examples are only used to illustrate the present invention and should not and will not limit the present invention described in detail in the claims.

[0026] A high CTI flame-retardant and high-temperature resistant nylon composite material comprises the following raw material components in parts by weight: 50-80 parts of high-temperature resistant nylon, 5-30 parts of fiber, 5-15 parts of flame retardant, 1-5 parts of synergist, 3-5 parts of toughening agent, and 0.1-2 parts of heat stabilizer; the fiber is one or more of carbon fiber and glass fiber; the flame retardant is one or more of aluminum hypophosphite and silsesquioxane; the synergist is nano-silica or nano-silica masterbatch.

[0027] The preparation method of the high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0028] S1: Weigh the raw materials of each component according to weight, and evenly mix the high temperature resistant nylon, flame retardant, synergist, toughening agent and thermal stabilizer in a high-speed mixer to obtain a stirred mixture;

[0029] S2: the stirred mixture obtained in step S1 is fed into the main feeding hopper of a twin-screw extruder, the fiber is fed into the fiber inlet of the twin-screw extruder, and the material is mixed and extruded through the twin-screw extruder;

[0030] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0031] The high CTI flame-retardant and high-temperature resistant nylon composite material of this embodiment has excellent CTI resistance, corrosion resistance, flame retardancy and mechanical properties. The material can be used to manufacture components such as electrode sheets and damping sheets for new energy vehicles, meeting the CTI resistance, flame retardancy, high temperature resistance, high strength, corrosion resistance, electromagnetic interference resistance and other properties required by materials in this field, and has good stability, reliability and long life cycle. The addition of a specific proportion of carbon fiber and alkali-free glass fiber to the material can not only play an excellent reinforcing and modifying role, but also improve the mechanical properties, chemical corrosion resistance and good thermal conductivity of the composite material. At the same time, the material can not only greatly improve the flame retardancy of the composite material, but also improve the CTI value of the material through the optimized combination of flame retardants and synergists.

[0032] Specifically, the silsesquioxane is octamethyl octasilsesquioxane, and the high temperature resistant nylon is PA10T.

[0033] In order to further improve the material performance, the toughening agent is one or more of olefin-acrylate-maleic anhydride copolymer and its derivatives. The use of multi-polymer toughening agents can significantly improve the high and low temperature impact resistance of the composite material, and can further improve the bonding performance between glass fiber and high temperature resistant nylon. Specifically, the toughening agent is ethylene-acrylate-maleic anhydride copolymer.

[0034] In order to further improve the material performance, the thermal stabilizer is bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, or a combination of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl tin mercaptan. The thermal stabilizer uses a combination of piperidinyl dioic acid ester and methyl tin mercaptan, which further improves the thermal stability of the composite material under high temperature environment or wet heat aging.

[0035] The composite material includes the following raw material components in parts by weight: 73 to 74.5 parts of high temperature resistant nylon, 30 parts of fiber, 8 parts of flame retardant, 1.5 parts of synergist, 5 parts of toughening agent and 1.2 parts of heat stabilizer.

[0036] Wherein, in step S2, the temperature of each zone of the twin-screw extruder is set at 290-350°C, and the main engine speed is 300-1000rpm. Specifically, in step S2, the temperature of each zone of the twin-screw extruder is set at 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, the die is 325°C, the main engine speed is 750rpm, the main feed speed is adjusted to control the amount of the mixture added, and the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added.

[0037] Example 1

[0038] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0039] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed and uniformly mixed in a high-speed mixer to obtain a stirred mixture;

[0040] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, and the main engine speed is 750rpm. The main feeding speed is adjusted to control the amount of the mixture added, and the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added. The materials are mixed and extruded through the twin-screw extruder;

[0041] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0042] Example 2

[0043] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0044] S1: 73 parts by weight of PA10T, 8 parts by weight of aluminum hypophosphite, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed and mixed in a high-speed mixer to obtain a stirred mixture;

[0045] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder, and the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, and the main engine speed is 750rpm. The main feeding speed is adjusted to control the amount of the mixture added, and the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added. The materials are mixed and extruded through the twin-screw extruder;

[0046] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0047] Example 3

[0048] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0049] S1: Weigh 74.5 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1 part by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan, and mix them in a high-speed mixer to obtain a stirred mixture;

[0050] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0051] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0052] Example 4

[0053] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0054] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyloctasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, and 1.2 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate were weighed and mixed in a high-speed mixer to obtain a stirred mixture;

[0055] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0056] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0057] Example 5

[0058] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0059] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed and uniformly mixed in a high-speed mixer to obtain a stirred mixture;

[0060] S2: The stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 30 parts by weight of carbon fiber are fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0061] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0062] Example 6

[0063] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0064] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed and uniformly mixed in a high-speed mixer to obtain a stirred mixture;

[0065] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 30 parts by weight of alkali-free glass fiber is fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is set to 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0066] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0067] Example 7

[0068] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0069] S1: Weigh 50 parts by weight of PA10T, 4 parts by weight of aluminum hypophosphite, 1 part by weight of octamethyl octasilsesquioxane, 1 part by weight of nano-silica, 3 parts by weight of ethylene-acrylate-maleic anhydride copolymer, and 0.1 part by weight of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and mix them in a high-speed mixer to obtain a stirred mixture;

[0070] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 5 parts by weight of alkali-free glass fiber is fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, the die opening is set to 325°C, the main engine speed is set to 300rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0071] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0072] Example 8

[0073] A method for preparing a high CTI flame retardant and high temperature resistant nylon composite material comprises the following steps:

[0074] S1: 80 parts by weight of PA10T, 10 parts by weight of aluminum hypophosphite, 5 parts by weight of octamethyl octasilsesquioxane, 5 parts by weight of nano-silica, 4 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 1.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.2 parts by weight of methyl tin mercaptan were weighed and uniformly mixed in a high-speed mixer to obtain a stirred mixture;

[0075] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 20 parts by weight of alkali-free glass fiber is fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, the die opening is set to 325°C, the main engine speed is set to 300rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0076] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a high CTI flame-retardant and high-temperature resistant nylon composite material.

[0077] Comparative Example 1

[0078] A method for preparing a PA10T composite material comprises the following steps:

[0079] S1: 103 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed, and the resulting stirred mixture was uniformly mixed in a high-speed mixer;

[0080] S2: The stirred mixture obtained in step S1 is put into a twin-screw extruder for mixing and extrusion, and the temperatures of each zone of the twin-screw extruder are set to 290° C., 300° C., 325° C., 330° C., 330° C., 330° C., 330° C., 325° C., 325° C., and the die is set to 325° C., the main engine speed is 750 rpm, and the main feed speed is adjusted to control the amount of the mixture added;

[0081] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a PA10T composite material.

[0082] Comparative Example 2

[0083] A method for preparing a PA10T composite material comprises the following steps:

[0084] S1: 81 parts by weight of PA10T, 1.5 parts by weight of nano-silica, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed and mixed uniformly in a high-speed mixer, and the obtained stirred mixture was fed into the main feeding hopper of a twin-screw extruder;

[0085] S2: The stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, and the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added;

[0086] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a PA10T composite material.

[0087] Comparative Example 3

[0088] A method for preparing a PA10T composite material comprises the following steps:

[0089] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of nano-silica, 5 parts by weight of methyl methacrylate-butadiene-styrene copolymer MBS, 0.8 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan were weighed, and the mixture was uniformly mixed in a high-speed mixer to obtain a stirred mixture;

[0090] S2: The stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 30 parts by weight of carbon fiber are fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0091] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a PA10T composite material.

[0092] Comparative Example 4

[0093] A method for preparing a PA10T composite material comprises the following steps:

[0094] S1: 73 parts by weight of PA10T, 6 parts by weight of aluminum hypophosphite, 2 parts by weight of octamethyl octasilsesquioxane, 1.5 parts by weight of antimony trioxide, 5 parts by weight of ethylene-acrylate-maleic anhydride copolymer, and 1.2 parts by weight of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate were weighed and mixed in a high-speed mixer to obtain a stirred mixture;

[0095] S2: the stirred mixture obtained in step S1 is put into the main feeding hopper of a twin-screw extruder, and 15 parts by weight of carbon fiber and 15 parts by weight of alkali-free glass fiber are respectively fed into the fiber inlet of the twin-screw extruder; the temperatures of each zone of the twin-screw extruder are set to 290°C, 300°C, 325°C, 330°C, 330°C, 330°C, 330°C, 325°C, 325°C, and the die is set to 325°C, the main engine speed is 750rpm, the main feeding speed is adjusted to control the amount of the mixture added, the glass fiber roll speed is adjusted to control the amount of hydrolysis-resistant glass fiber added, and the materials are mixed and extruded through the twin-screw extruder;

[0096] S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain a PA10T composite material.

[0097] Example 9 Performance Test Experiment

[0098] The particles prepared in the above 8 embodiments and 4 comparative examples were injection molded on an injection molding machine, and the specimens were placed in a constant temperature and humidity chamber with a humidity of 50% and 23° C. for 48 hours for testing.

[0099] Tensile strength: tested according to ISO 527 standard, tensile speed 5mm / min;

[0100] Notched impact strength: tested according to ASTM D256 standard;

[0101] Corrosion resistance: Tested according to GB / T 11547-2008 standard, after soaking in 80℃ saturated salt water for 24 hours, the dimensional change is examined, ≤0.25% is qualified, >0.25% is unqualified;

[0102] CTI resistance: tested according to ASTM D2303-2013 standard, constant voltage 1.5kV;

[0103] Flame retardant performance: tested according to UL94 standard, thickness 0.8mm;

[0104] The properties of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in the following table:

[0105]

[0106]

[0107] By comparing the data in the table, it can be seen that when carbon fiber / alkali-free glass fiber is not added, the composite material fails the corrosion resistance test, and the strength index is also much lower than that of the fiber modified system; when no flame retardant is added, the composite material is only V2 grade under the fiber reinforced system; when no synergist is present, the flame retardant level of the composite material is V1, while the high temperature resistant nylon / aluminum hypophosphite / octamethyl octasilsesquioxane / nano-silica combination system reaches V0 grade; when the conventional methyl methacrylate-butadiene-styrene copolymer MBS toughening agent is used, the mechanical property index is lower than that of the ethylene-acrylate-maleic anhydride copolymer system in the present invention; when the conventional antimony trioxide synergist is used instead of nano-silica, it is disadvantageous to the CTI resistance, flame retardant properties and mechanical properties of the composite material system.

[0108] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high CTI flame retardant and high temperature resistant nylon composite material, characterized in that: The invention comprises the following raw material components in parts by weight: 73 parts of PA10T, 30 parts of carbon fiber, 6 parts of aluminum hypophosphite, 2 parts of octamethyl octasilsesquioxane, 1.5 parts of nano silicon dioxide, 5 parts of ethylene-acrylate-maleic anhydride copolymer, 0.8 parts of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, and 0.4 parts by weight of methyl tin mercaptan.

2. The method for preparing a high CTI flame retardant and high temperature resistant nylon composite material according to claim 1, characterized in that: The following steps are involved: S1: Weigh the raw materials of each component according to weight, and evenly mix PA10T, aluminum hypophosphite, octamethyl octasilsesquioxane, nano-silica, ethylene-acrylate-maleic anhydride copolymer, bis(1,2, 2, 6, 6-pentamethyl-4-piperidyl) sebacate, and methyl tin mercaptan in a high-speed mixer to obtain a stirred mixture; S2: the stirred mixture obtained in step S1 is fed into the main feeding hopper of a twin-screw extruder, the carbon fiber is fed into the fiber inlet of the twin-screw extruder, and the material is mixed and extruded through the twin-screw extruder; S3: The product melt-extruded by the twin-screw extruder is subjected to water cooling, air cooling and drying, pelletizing, vibration screening, homogenization, and drying to obtain the high CTI flame-retardant and high-temperature resistant nylon composite material.

3. The preparation method according to claim 2, characterized in that: In step S2, the temperature of each zone of the twin-screw extruder is set at 290-350° C., and the main engine speed is set at 300-1000 rpm.

4. Application of the high CTI flame retardant and high temperature resistant nylon composite material as claimed in claim 1 in new energy vehicles.

Citation Information

Patent Citations

  • Semi-aromatic polyamide resin with high CTI value as well as preparation method and application thereof

    CN112724400A

  • Red phosphorus flame-retardant polyamide composition with high tracking resistance as well as preparation method and application of red phosphorus flame-retardant polyamide composition

    CN114672160A

  • Halogen-free flame-retardant master batch and preparation method thereof, and glass fiber reinforced nylon material and preparation method thereof

    CN110922747A